Lordship and Humanity Principles for The Peace of Indonesia: An Integrative Study of Theology and Ideology - Lumintang, Stevri Penti Novri Indra (Analisa: Journal of Social Science and Religion, 2021)
This study is stimulated by the background of the gap regarding the understanding and application between the Indonesian ideology of Pancasila and theology (religion) among both Muslims and Christians. This research aimed to study the integration between Christian theology and the Indonesian ideology of Pancasila. This research was based upon the naturalistic paradigm with a qualitative approach and integrative research method to find a model for solving religious intolerance and violence, which is often manipulated by political interests. This integrative study, especially integral dialectical synthesis, is to find a holistic knowledge of the doctrine of the principle of One Lordship, just and civilized humanity according to Christian theology and ideology of Pancasila as a model of integration. The integrative study between theology and ideology confirms that each of the five principles of Pancasila is theological, and even a mandate that believers (the Christians community) must obey. The relationship between Christian theology and the ideology of Pancasila is an integrative relationship because God and humanity are also integrative. These findings suggest that all Christians live in love and respect to their fellow humans, both Christian and non-Christian. Loving God and others means loving the Indonesian people by participating in overcoming the nation's problems and building the Indonesian nation's welfare for the welfare of the nation is our (all Indonesian citizens) wellbeing.